2014
DOI: 10.1093/jnci/dju147
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cervical Cancer Displaying Tumor-Related Leukocytosis: A Distinct Clinical Entity With Radioresistant Feature

Abstract: TRL is associated with resistance to radiotherapy among cervical cancer patients, and MDSC-targeting treatments may have therapeutic potential in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(156 citation statements)
references
References 19 publications
12
141
1
2
Order By: Relevance
“…G-CSF expression has been detected in the tumors of many solid malignancies, including breast cancer (46)(47)(48)(49), and tumors that express G-CSF have been found to be more aggressive and associated with increased likelihood of recurrence (46). G-CSF can induce T-cell tolerance and has been shown to drive MDSC development from human hematopoietic stem cells cultured in vitro (31,49).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF expression has been detected in the tumors of many solid malignancies, including breast cancer (46)(47)(48)(49), and tumors that express G-CSF have been found to be more aggressive and associated with increased likelihood of recurrence (46). G-CSF can induce T-cell tolerance and has been shown to drive MDSC development from human hematopoietic stem cells cultured in vitro (31,49).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is produced by a tumor and in turn induces the production of myeloid-derived suppressor cells (MDSCs). These MDSCs cause rapid progression of cervical cancer and leukocytosis and radioresistance [18]. Mabuchi et al depleted MDSCs, which succeeded in inhibiting the progression of cervical cancer and leukocytosis and enhancing radiosensitivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…These MDSCs cause rapid progression of cervical cancer and leukocytosis and radioresistance [18]. Mabuchi et al depleted MDSCs, which succeeded in inhibiting the progression of cervical cancer and leukocytosis and enhancing radiosensitivity [18]. MDSCs have been found in bone marrow, blood, and the spleen of individuals with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recently demonstrated that MDSCs can suppress T cells in the spleen promoting tumor immunosuppression (22). Accordingly, splenectomy in mice can change the amount of tumorinfiltrating MDSCs, promoting tumor regression in murine models of cancer (42). Therefore, MDSCs in cancer patients may affect tumorigenesis by acting in multiple sites, not only in the tumors.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%